2021
DOI: 10.1029/2020jf006003
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Response of West and East Antarctic Ice Sheets to Glacial Isostatic Adjustment

Abstract: The majority of the West Antarctic ice sheet (WAIS) as well as some basins of the East Antarctic ice sheet (EAIS) are grounded below present-day sea level on an inland sloping bed (Fretwell et al., 2013;Morlighem et al., 2019). Such a configuration makes these basins particularly vulnerable to rapid grounding-line retreat that may lead to the so-called ice marine ice sheet instability (MISI) in case of weak or absence of buttressing (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 118 publications
(329 reference statements)
1
18
0
Order By: Relevance
“…The resulting reduction of relative sea level at the grounding line may stabilize its retreat, providing a negative feedback (Barletta et al, 2018;DeConto et al, 2021;Gomez et al, 2010Gomez et al, , 2015Larour et al, 2019;Pollard et al, 2017) showed that these effects do little to slow the pace of retreat until after the mid-twenty-third century in the Amundsen Sea region. Coulon et al (2021) also find that the West-Antarctic ice sheet destabilizes for high-forcing regardless of the mantle viscosity. At the same time, Kachuck et al (2020) and Pan et al (2022) indicate that the weak viscosity in West-Antarctica might significantly reduce the West-Antarctic contribution over the next 150 yr, because the rapid bedrock uplift compensates the grounding line retreat.…”
Section: What If the Major Ice Shelves Break Up?mentioning
confidence: 62%
See 1 more Smart Citation
“…The resulting reduction of relative sea level at the grounding line may stabilize its retreat, providing a negative feedback (Barletta et al, 2018;DeConto et al, 2021;Gomez et al, 2010Gomez et al, , 2015Larour et al, 2019;Pollard et al, 2017) showed that these effects do little to slow the pace of retreat until after the mid-twenty-third century in the Amundsen Sea region. Coulon et al (2021) also find that the West-Antarctic ice sheet destabilizes for high-forcing regardless of the mantle viscosity. At the same time, Kachuck et al (2020) and Pan et al (2022) indicate that the weak viscosity in West-Antarctica might significantly reduce the West-Antarctic contribution over the next 150 yr, because the rapid bedrock uplift compensates the grounding line retreat.…”
Section: What If the Major Ice Shelves Break Up?mentioning
confidence: 62%
“…Coulon et al. ( 2021 ) also find that the West‐Antarctic ice sheet destabilizes for high‐forcing regardless of the mantle viscosity. At the same time, Kachuck et al.…”
Section: Antarcticamentioning
confidence: 95%
“…This can lead to additional biases in ice-stream dynamics and poleward moisture transport, respectively. Additionally, glacial-isostatic adjustment 51 other than vertical bedrock response by elastic lithosphere is not fully implemented in LOVECLIP. Nevertheless, our simulations also illustrate that ice-sheet ocean/atmosphere coupling, which can account for individual mass balance differences of 0.5-0.8 cm/year SLE over the next ~100 years (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The re‐advance was in part due to swift glacioisostatic rebound (cf. Coulon et al., 2021; Lowry et al., 2020), a process aided by the region's low‐viscosity mantle (Whitehouse et al., 2019) and likely to be accommodated upon pre‐existing crustal faults, as observed in the Lambert Graben (Phillips & Läufer, 2009). Our proposed graben‐bounding faults would provide a tectonic control on the glacioisostatic adjustment of the Siple Coast region.…”
Section: Discussionmentioning
confidence: 99%